Pengaruh Marchandise, Store Atmosphere Dan Price Discount Terhadap Impulse Buying Studi Pada Konsumen Ramayana Department Store Malang - Deddy Rahman Saputra; Nur Hidayati; M. Ridwan Basalama (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
AbstractThe purpose of this research is to determine the influence of merchandise, an atmosphere store and price discount against impulse buying. The population of this study is the entire consumer ramayana department store poor. The sample sampling could be taken using the acidentity al sampling method where sample taking is based on chance and total getting from the valuation is 100 samples of people. It uses multiple linear regression models. In this research suggests merchandise, sotre atmospher and price discount influence impulse buying. Merchandise bears a significant positive impact on impulse playing. Atmosphere store has a significant positive effect on impulse buying. Price discount has a negative impact on impulse buying. Keywords : Merchandise, Store Atmosphere, Price Discount, Impululse Buying.